Taking a Long View in Child Welfare: How Can We Evaluate Intervention and Child Wellbeing Over Time?. (10th June 2013) - McGhee, Janice; Mitchell, Fiona; Daniel, Brigid; Taylor, Julie
<x xml:space="preserve">Abstract</x> This paper synthesises ideas generated from an international knowledge exchange seminar series to explore the potential and pitfalls in utilising routine administrative data and survey data for longitudinal research about children involved in public child welfare services. Methodological, technical and ethical issues are explored, including the challenges in capturing the nature, focus and intensity of intervention. It is suggested that assessing child wellbeing across a range of dimensions in the short, medium and long term may provide a better conceptual basis for research than defining specific outcomes. Copyright © 2013 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2268-blk-0001" position="anchor" orientation="portrait"> 'Synthesises ideas generated from an international knowledge exchange seminar series' </boxed-text> Key Practitioner Messages: In responding to child maltreatment, it is crucial to record and understand the social context. Information systems can be used beyond individual cases, disciplines and jurisdictions. Their potential when combined will help us understand child maltreatment to a greater degree. Child protection work is complex and practice is not straightforward. Understanding what works best, for whom and in what circumstances can be enhanced by looking at multiple disciplines over long periods of time.